Empat Manuskrip Alquran di Subang Jawa Barat (Studi Kodikologi Manuskrip Alquran) - Jajang A. Rohmana (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2018)
The article focuses on four qur’anic manuscripts in Subang, West Java. I will analyze the material aspect of the manuscripts and its writing styles, using the codicological approach. This study shows that three manuscripts used European paper and containing “Concordia” watermark which was produced around the late 19th century. These three manuscripts might be written later at the beginning of the twentieth century. Meanwhile, the last one who used bark paper of daluang cannot be estimated its dating. The writing of four manuscripts used Naskhi style. There are also some errors in handwriting. Moreover, the manuscripts used rasm imla’i as same as classical mushaf in the archipelago. These manuscripts are different with palace manuscripts that generally used beauty illuminations and scribes. This study is not only critical to give another perspective on the spread of qur’anic manuscripts in Southeast Asia, particularly in West Java but also to strengthen the distinctive feature on material manuscripts, rasm, and illumination of qur’anic manuscripts in the Archipelago. These four qur’anic manuscripts show the importance of the role of the Qur’an in strengthening Islam in the society through the scribe of qur’anic manuscripts and its use in the learning of Islam.